2021
DOI: 10.3390/ijms222011245
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Modulates the Efficacy of Electroporation and Calcium Electrochemotherapy

Abstract: Electroporation is influenced by the features of the targeted cell membranes, e.g., the cholesterol content and the surface tension of the membrane. The latter is eventually affected by the organization of actin fibers. Atorvastatin is a statin known to influence both the cholesterol content and the organization of actin. This work analyzes the effects of the latter on the efficacy of electroporation of cancer cells. In addition, herein, electroporation was combined with calcium chloride (CaEP) to assess as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Indeed, in EPP85-181RDB cells, peripherally aligned F-actin bers were disrupted following the nsPEF treatment, which reduced the surface tension of the membrane. The surface tension is also affected by the lipid composition of the cancer cell membrane [39]. Our molecular dynamics simulations showed that the reduced surface tension of the membrane leads to its invagination of the membrane and further the MVs release.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, in EPP85-181RDB cells, peripherally aligned F-actin bers were disrupted following the nsPEF treatment, which reduced the surface tension of the membrane. The surface tension is also affected by the lipid composition of the cancer cell membrane [39]. Our molecular dynamics simulations showed that the reduced surface tension of the membrane leads to its invagination of the membrane and further the MVs release.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, in EPP85-181RDB cells, peripherally aligned F-actin fibers were disrupted following the nsPEF treatment, which reduced the surface tension of the membrane. The surface tension is also affected by the lipid composition of the cancer cell membrane 38 . Our molecular dynamics simulations showed that the reduced surface tension of the membrane leads to its invagination of the membrane and further the MVs release.…”
Section: Discussionmentioning
confidence: 99%
“…The first effect was widely described in the Jurkat cell line, in which the nanosecond pulses induced the permeabilization of the mitochondrial outer membrane and, therefore, the release of cytochrome c and reactive oxygen species to the cytoplasm ( 138 ). After the disruption of cell membrane integrity, the cell increases the biosynthesis of the components of its cytoskeleton ( 139 ). However, in short-term response, Kiełbik et al.…”
Section: Physical Methods and Their Mechanismsmentioning
confidence: 99%